Evaluation of Scout Activities as a Means of Character Formation at the Junior High School Level: An Analytical Review - Novita Ayu Putri; Abdul Hamid K.; Samsidar Tanjung (Randwick International of Education and Linguistics Science Journal, 2024)
This research aims to find out: the context of Scout Extracurriculars in shaping student character; input to Scout Extracurriculars in shaping student character; the process of Scout Extracurriculars in shaping student character; and projects for Scout Extracurriculars in shaping student character. This research uses evaluation research. Research activities to collect data and present accurate and objective information regarding Scout extracurriculars at SMP Negeri 35 Medan based on established criteria. The results of this evaluation research show that the context aspect shows that the character of Scout students has been implemented well, but the support from the preparation of Scout extracurricular activities and the input aspect have been implemented well with the components in scouting development and aspects of the process of forming the character of Scout students from the implementation of Scout extracurricular activities. Not yet fully included in the planning document, the product aspects of Scout student character formation in the implementation of the evaluation are carried out only independently based on the coach's observations. The usefulness of the results of this evaluation will direct coaches to realize complex learning outcomes and build growth in learning experiences for students.